Kinect hacks - St. Jean, Jared (Hacks series., 2012)
"Set up a development environment in Windows, Mac OS X, or Linux; build special effects apps with tools such as Synapse and Cinder; create gestural interfaces to integrate and control digital music components; capture the realistic motions of a 3D model with NI mate, Blender, and Animata; design gesture-based games with the ZigFu SDK; recreate the dimensions of any room in real time, using RGBDemo; use gestures to navigate robots and control PC interfaces"--Page 4 of cover.